(untitled) (International Journal of Physiotherapy, 2026)
Background: Dependence on prescription opioid analgesics has become an increasing public health concern in the United States. Opioids are often prescribed to treat moderate to severe pain. Experts agree that a multidisciplinary approach should be used to treat OAD. Research has shown that chronic neck pain is best treated with a multimodal approach. MSI is an approach that incorporates exercise and education. This study aimed to determine if a collaborative approach by a pain management specialist and a physical therapist, using the MSI approach, can result in pain reduction, improved function, and decreased opioid consumption in a patient who is determined to be at risk of opioid abuse and dependence by the pain specialist. Case Description: This case involves a woman in her early fifties who presented to outpatient physical therapy following referral from a pain management specialist for longstanding neck and shoulder pain that began after a motor vehicle accident approximately five years earlier. The medical diagnosis was cervical spondylosis without radiculopathy. The patient was identified as being at risk for opioid dependence based on an elevated score on a validated patient-reported screening questionnaire. Physical therapy evaluation using the Movement System Impairment (MSI) framework resulted in movement system diagnoses of Cervical Extension–Rotation Syndrome and Scapular Depression with Anterior Tilt and External Rotation Syndrome. Intervention consisted of a collaborative interdisciplinary approach involving a pain management specialist and a physical therapist, with weekly physical therapy sessions over six weeks focused on movement correction, postural education, and a structured home exercise program, along with a planned reduction in opioid use and initiation of non-opioid analgesics. Outcomes included reductions in pain intensity at rest and with activity. Functional disability improved over the six-week intervention period based on a validated neck-specific disability measure. Complete discontinuation of tramadol use by week four, with no opioid consumption reported during the final two weeks of care. Outcomes: From the initial visit to 6 weeks, the patient’s pain at rest was reduced from 4/10 to 0-1/10 on NRS, pain with movement was reduced from 6/10 to 0-1/10, pain after driving more than 30 minutes was reduced from 5/10 to 1/10, and the pain after work was reduced from 10/10 to 3/10. On NDI, her disability was reduced by 16% at the end of 6 weeks. She did not consume any tramadol from week 4 to week 6. Conclusion: The case report suggests that Physical Therapy can be considered one of the disciplines to treat opioid analgesic dependence. The MSI approach for neck and scapular syndromes was effective in treating this patient. However, Additional studies are needed to examine further the reliability and clinical utility of this assessment approach in broader patient populations. The cervical examination tests included the efficacy of the recommended treatment for cervical diagnosis.